Os espaços poéticos de um cronista contador - Oliveira, Joana Leopoldina de Melo (2009)
This study discusses chronicler Rubem Braga and his chronicles published in O Estado de São Paulo newspaper (supplement Caderno 2), from 1988 to 1990. The analysis of the 84 chronicles focuses on the study of poetic spaces, mainly based on Gaston Bachelard s book The Poetics of Space. Narrator s characteristics are also shown in the analyzed chronicles, as he resembles a traditional storyteller, even though participates in a genre that belongs to a modern vehicle: the newspaper. The storyteller-chronicler moves in time and space, reporting his experiences to the readers, and also travels inside of himself, discovering places which were kept in his memory